Geotechnical parameter assessment of sediment deposit: A case study in Pasakha, Bhutan. Issue 1 (1st January 2021) - Tempa, Karma; Chettri, Nimesh; Sarkar, Raju; Saha, Sunil; Gurung, Lily; Dendup, Tshering; Nirola, Bhawani Shankar
Abstract: The research area falls at the downstream level of Bhalujhora landslide area in Alay which is located in Pasakha, Bhutan. Local Government authority proposed for construction of custom station between the commercial town Phuentsholing and Pasakha Industrial estate. However, downstream region which connects the core town to industrial estate are severely affected by the flash floods every year and the runoff causes huge sediment deposits leading risk for community and substantial damages to the infrastructures. The site is seasonally eroded and subsequently deposited by the sediments from upstream. Although, the formation level for infrastructure are proposed on the deposit layer, the assessment of soil parameters is necessary for design and planning to ensure the overall safety and long-term economic benefits. Through this study, the subsurface soil parameters are assessed by in-situ open pit investigation, geophysical survey and Standard Penetration Test (SPT), while the engineering properties of the sediment deposits were determined from laboratory tests. The field investigation was important to decide the suitability of foundation type and depth. Further, soil parameters were determined to classify the soil type, understand permeability characteristics, and predict shear strength parameters and compaction behaviour. The result shows that the sediments consist of mixture of natural aggregates and sand mixed with silt and clay. An estimate of sediment accumulation was carried out to determine the volume of the sediment deposited. The outcome will allow the relevant stakeholders to decide the management of the risk from this future disaster and propose alternative use of the sediment materials in road works.